Returning to Nothing : The Lost of Malay Settlement in Pasir Mas, Kelantan - Azli, Abdullah; Julaihi, Wahid (GKAK UNMER Malang, 2022)
Natural calamities such as earthquakes, landslides, windstorms, and floods are considered disasters according to the degree of disruption they caused to the human population, built environment, or natural ecosystem. Natural disasters are a common occurrence in rural settlements of Malaysia, affecting the lives of the rural population and damaging the rural settlements, agriculture, roads, drainage schemes, and other infrastructure. This threat continues to exist, and disasters are still wreaking havoc in rural areas. However, this disaster is compounded by the current rate of urbanization in the region. Human life conjures a spatial location due to the unique combination of movement and strength that characterizes humans. Humans, unlike trees, are not stationary; yet they require more manmade shelters than other animals, and communities. Humans, in particular, share their space. A loss narrative defines today's place literature: specifically, the loss of the correct link between place and meaning (Cox, 1968; Lynch, 1972; Jacobs & Appleyard, 1987; Kunstler, 1993). Simultaneously, this article aims to investigate the disappearance of Malay settlements and discuss some of the implications. In February 2021. a landslide event took place in Pasir Mas, Kelantan. Researchers implemented on observation, mapping technique using Google Earth and Autocad 2018 software and visual analysis approach. It is an area where researchers used to spend their youth. The objective of this paper is to provide a perspective on the disappearance of Malay settlement by studying two theories, namely natural calamity and Malay settlement in order to discuss the finding about the reflection of place, and secondly, the loss of Malay culture crisis.